1984
DOI: 10.1177/104438948406500105
|View full text |Cite
|
Sign up to set email alerts
|

The Identity of Transracial Adoptees

Abstract: A study identifies familial and contextual factors that may influence the development of racial self-perceptions among black children whose major reference groups are white. It also suggests responsibilities for transracial adoptive families and agencies that provide service for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…Findings also suggest that transracial adoptees who were being raised in an integrated area, who attended a racially integrated school, and who had parents who acknowledged the child's racial background tended to describe themselves positively as an African American (McRoy, et al, 1984). Similar to their findings in previous research (McRoy, et al, 1982), the authors stress the importance and influence of a transracially-adopted child's psychosocial environment on his/her racial identity.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Findings also suggest that transracial adoptees who were being raised in an integrated area, who attended a racially integrated school, and who had parents who acknowledged the child's racial background tended to describe themselves positively as an African American (McRoy, et al, 1984). Similar to their findings in previous research (McRoy, et al, 1982), the authors stress the importance and influence of a transracially-adopted child's psychosocial environment on his/her racial identity.…”
supporting
confidence: 77%
“…It explored identity formation and related issues post-adolescence, when aspects of identity have been more fully explored and integrated into one's sense of self. However, unlike previous research examining identity formation among transracial adoptees (Andujo, 1988;Bagley, 1991;Brooks & Barth, 1999;Hollingsworth, 1997;Locust, 2000;McRoy, et al, 1982McRoy, et al, , 1984Peterson, 2002;Shireman, 1988;Shireman & Johnson, 1975Vroegh, 1997), this study did not define the construct of identity nor did it use empirically-based, standardized measures to capture data related to identity formation or measure the strength of one's racial/ethnic identity.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, if black children were to be able to develop a positive black identity and successfully handle encounters with racism, ABSWAP claimed, they needed to grow up with parents who could imbue their child with the necessary strategies (Gaber, 1994;Kirton, 2000). Following these statements, an increasing number of local child welfare authorities and organisations took a critical stance on transracial adoptions, and British and US adoption research came to be dominated by studies concerned with whether transracially adopted children identified with their own race or with that of their adoptive parents (Gill and Jackson, 1983;McRoy et al, 1984;Simon and Altstein, 1992;DeBerry et al, 1996;Hollingsworth, 1997).…”
Section: Rights and Cultural Backgroundsmentioning
confidence: 99%